Effectivity of a Program for the Control and Prevention of COVID-19 Healthcare-Associated Infections in a Spanish Academic Hospital. Issue 4 (June 2021) - Gras-Valentí, Paula; Mora-Muriel, Juan G.; Chico-Sánchez, Pablo; Algado-Sellés, Natividad; Soler-Molina, Victor M.; Hernández-Maldonado, María; Lameiras-Azevedo, Ana S.; Jiménez Sepúlveda, Natali J.; Gómez Sotero, Isel L.; Villanueva-Ruiz, César O.; Barrenengoa-Sañudo, Julio; Fuster-Pérez, Marina; et al.
Abstract : Background: Although recommendations to prevent COVID-19 healthcare-associated infections (HAIs) have been proposed, data on their effectivity are currently limited. Objective: The aim was to evaluate the effectivity of a program of control and prevention of COVID-19 in an academic general hospital in Spain. Methods: We captured the number of COVID-19 cases and the type of contact that occurred in hospitalized patients and healthcare personnel (HCP). To evaluate the impact of the continuous use of a surgical mask among HCP, the number of patients with COVID-19 HAIs and accumulated incidence of HCP with COVID-19 was compared between the preintervention and intervention periods. Results: Two hundred fifty-two patients with COVID-19 have been admitted to the hospital. Seven of them had an HAI origin (6 in the preintervention period and 1 in the intervention period). One hundred forty-two HCP were infected with SARS-CoV-2. Of them, 22 (15.5%) were attributed to healthcare (2 in the emergency department and none in the critical care departments), and 120 (84.5%) were attributed to social relations in the workplace or during their non–work-related personal interactions. The accumulated incidence during the preintervention period was 22.3 for every 1000 HCP and 8.2 for every 1000 HCP during the intervention period. The relative risk was 0.37 (95% confidence interval, 0.25 to 0.55) and the attributable risk was −0.014 (95% confidence interval, −0.020 to −0.009). Conclusions: A program of control and prevention of HAIs complemented with the recommendation for the continuous use of a surgical mask in the workplace and social environments of HCP effectively decreased the risk of COVID-19 HAIs in admitted patients and HCP.